A PALEOMAGNETIC ANALYSIS OF CAMBRIAN TRUE POLAR WANDER - Meert J.G. (My University, 1999)
The latest Neoproterozoic through Cambrian is one of the most remarkable intervals in geologic time. Tectonically, the period from 580 to 490 Ma marks a time of rapid plate reorganization following the final stages of supercontinental breakup and Gondwana assembly. The apparent speed at which this reorganization occurred led some to propose a link between tectonic events, biologic changes and climatic changes. One of the more intriguing proposals is that the tectonic changes were triggered by an episode of inertial interchange true polar wander (IITPW) which resulted in a rapid (6°/m.y.) shift of the spin axis relative to the geographic reference frame. IITPW is a special case of true polar wander (TPW) that makes specific demands on the length of apparent polar wander paths (APWPs) recording the motion. Specifically, each path must allow for ∼90° of synchronous motion during the interval from 523 to 508 Ma. A review of paleomagnetic data for Laurentia, Baltica, Siberia and Gondwana indicates that none of the APWPs approaches the necessary length, each path is of a different length and the apparent motions are non-synchronous. Collectively, these observations negate the premise of a Cambrian IITPW event. Since the IITPW hypothesis was proposed as an alternative to rapid plate motion of Laurentia and Gondwana during the Neoproterozoic–Cambrian interval, any alternative model must account for this rapid motion. I suggest that a reasonable explanation for `anomalously' high rates of plate motion for some continents, possibly on the order of 20–40 cm yr−1, is enhanced plate motion driven by lower-mantle thermal anomalies and possibly true polar wander. In fact, the enhanced plate motions driven by these lower-mantle sources may provide a dynamic feedback triggering true polar wander.
Keywords: Cambrian; Paleozoic::Cambrian; Палеозой::Кембрийская